Black Popular Culture : A project by Michele Wallace - A. Baker Jr., Houston; Carby, Hazel V.; Davis, Angela Y.; Dent, Gina; Diawara, Manthia; Hall, Stuart; Jafa, Arthur; Rose, Tricia (Seattle; Dia Center for the Arts; Bay Press, 1992)
The eighth volume in the award-winning Discussions in Contemporary Culture series, Black Popular Culture examines the roles of artist and audience, producer and critic, and the synergistic relationship between black cultural expressions and their political, economic, and social contexts. An extraordinary array of critics, scholars, and cultural producers explore the multiple meanings of the cultural term "Black" and, in so doing, propose an inclusive arena of expression and political possibility within the context of black popular culture. Edited by Gina Dent. Contributions by Houston A. Baker Jr., Hazel V. Carby, Angela Y. Davis, Manthia Diawara, Stuart Hall, Arthur Jafa, Tricia Rose, et al.
English
Keywords: HM621-656 Sociology- Culture